Peningkatan Kompetensi Pengurus Koperasi Se-Provinsi Riau Melalui Pelatihan Akuntansi - Evi Marlina; Azhari, Intan Putri; Asnawi, Mizan; Putri, Adriyanti Agustina; Azmi, Zul; Rodiah, Siti; Suci, Rama Gita; Septian, Raja (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
Cooperatives are business entities whose members are individuals whose aim is to prosper its members based on kinship. Every year, cooperative management and supervisors prepare an accountability report that will be submitted at the annual member meeting (RAT). In compiling the accountability report, the accounting competencies of cooperative management are required to refer to the Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK-EMKM) and Permenkop no 12 of 2015 concerning cooperative financial reports. This service is carried out to improve the competence of cooperative management in Riau province in compiling financial reports. This activity was carried out at the Riau Province Cooperative and UKM Training UPT. The approach taken is workshops and training, namely by providing explanations of material in tutorials and discussions and providing examples of making good and correct cooperative financial reports in accordance with cooperative accounting standards